ANALISIS TOTAL FOSFAT, NITRAT DAN LOGAM TIMBAL PADA SUNGAI SAIL DAN SUNGAI AIR HITAM PEKANBARU - Suwandi, Yohanes; Bali, Subardi; ', Itnawita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Sail River and Air Hitam River are effluent from Siak River where around the two rivers many social activities such as lodging, stall, market, hospital, home industry and dump are founds. Waste from the activities is able to decrease water quality of the rivers. Water quality of the rivers can be evaluated based on Government Regulation No.82, 2001 and Riau Governor Decree No.8, 2001. Water sampling was conducted along both of the rivers at four stations from Oktober to Desember 2013. Samples were taken in two weather conditions i.e rain and dry season. The results of parameter like temperature, Biological Oxygen Demand (BOD) and turbidity in Sail river showed values which were above the limit but the results of Total Suspended Solid (TSS) and Chemical Oxygen Demand (COD) passed the limit of water quality. In Air Hitam river, all results of parameter were still above of the limit. The results of parameter like Phosphat and Pb at all stations at Sail river and Air Hitam rivers passed the limit, while of Nitrate result were still above the limit.